A critique of the socio-spatial debate and the publicness of urban space. Issue 3 (27th May 2018) - Wang, Yiming
ABSTRACT: Research on urban processes under capitalism and the resulting transformations of urban space is caught in a socio-spatial dualistic debate, which neglects the continuum and relativities of space. The author aims to extend this debate through an in-depth review and critique of the main perspectives on socio-spatial relations. He argues that in capitalist urban processes urban space plays a dual role as both the public sphere and arena of capital accumulation. However, importantly, this dual role has led to the multidimensional nature of the publicness of space which, in turn, collaboratively results in increasingly blurred boundaries between 'public' and 'private' in cities. To grapple with the new features of urban space for theory and empirical research, the article offers an alternative property rights approach. Rather than treating space as monolithic, the proposed property rights approach puts the case for analysing space as a continuum. On this basis, the author discusses how that approach can be used for empirical research.